Effect of a salt-reduction strategy on blood pressure and acceptability among customers of a food concessionaire in Lima, Peru - Reynoso-Marreros, Isabel A. (2018)
Aim: Limited information exists regarding the implementation of salt reduction strategies on collective food services, such as restaurants and food concessionaires. The present study aimed to assess the effect of a salt reduction strategy on blood pressure levels and food acceptability among customers of a food concessionaire. Methods: A quasi-experimental study with two phases was conducted. In the pre-intervention phase, the amount of salt used in food preparation was determined. In the intervention phase, a reduction of 20% in salt added to food preparations was implemented. Four hedonic tests and two blood pressure measurements were performed before and after the intervention implementation using standardised techniques. In addition, an evaluation of uneaten food was conducted daily on all customers' plates. Mixed linear regression models were generated to assess the effect of the intervention on blood pressure and acceptability. Results: A total of 71 workers were evaluated, mean age of 37.5 years, 57.8% females, who consumed the food of the concessionaire, on average, 4.4 (SD: 0.7) days per week. Systolic and diastolic blood pressure were reduced by 3.1 (P<0.001) and 2.9 (P<0.001) mmHg at the end of the study, respectively. The results of the hedonic tests and the uneaten food before and after the intervention did not vary significantly. Conclusions: The reduction of 20% of salt added to food from a concessionaire had a positive impact on the reduction of customers' blood pressure without reducing food acceptability. This strategy could be implemented in other contexts.